Taburan dan Populasi Ikan Air Tawar di Beberapa.Altitud di Taman Kinabalu Sabah, Malaysia. - Samat, Abdullah (1990)
A survey was conducted to study the distribution and population of freshwater fish fauna of the Kinabalu Park.. Fishes were sampled using electro shocker; the impact of water quality was also studied. Physical parameters were determined in-situ while several nutrient and heavy metal contents were analysed in the laboratory. A total of 22 species were found, representing5families. Rasbora hubbsi, Osteochilus spilurus and Nematabramis alestes are new listings for this area. Oreochromis mossambicus and Trichogaster trichopterus were not found although they had been reported previously. The distribution and population offish were found to vary according to altitude and several physical parameters of the waters.